Analisis Peran Kinerja Customer Service Dan Teller Terhadap Kepuasan Nasabah Bank - Evalin, Zuziana Zesaria; Sukartaatmadja, Iswandi; Mulyadi, Muhammad Noorman (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The principal problem of this study is Whether the role performance of customer service will increase customer satisfaction at Bank BJB Leuwiliang Bogor District? 1) what Is the role of the performance of the teller will increase customer satisfaction at Bank BJB Leuwiliang Bogor District? 2)what Is the role of the performance of the customer service and tellers to improve customer satisfaction of Bank BJB Leuwiliang Bogor District? . The purpose of this study, namely: 1) To find out whether the role performance of customer service will increase customer satisfaction at Bank BJB Leuwiliang Bogor Regency. 2)To find out whether the role performance of the teller will increase customer satisfaction at Bank BJB Leuwiliang Bogor Regency. 3)To find out whether the role performance of customer service and teller will increase customer satisfaction at Bank BJB Leuwiliang Bogor.This research use approach of kualititatif, and the analysis used is multiple linear regression . The sampling technique used is by distributing questionnaires to 100 customers of BJB Leuwiliang with the hope of answers the results of the questionnaires the customer can determine the performance of the customer service and tellers to improve customer satisfaction BJB Leuwiliang. Based on the results of this study, prove that the value R of 0.797 indicates the relationship between the variables of role performance of customer service and teller to the satisfaction of the customer is significant , the Variable Role Performance of Customer Service to the Satisfaction of the Customer Based on the results of testing for X1, i.e., the Role Performance of Customer Service obtained t count value that is 4.147, which means t count > t table (4.147 >2.01174) . And sig t < 0.05 (0.00 < 0.05). Then Ho is rejected and Ha accepted, so it can be concluded that the partial variables Role Performance of Customer service have a significant influence on the variable Customer Satisfaction. Variable Role Performance of the Teller to the Satisfaction of the Customer Based on the results of testing for X2, i.e., the Role Performance of the Teller obtained by value t calculate namely 3.242 which means t count > t table (3.242 > 2.01174). And sig t < 0.05 (0.002 < 0.05). Then Ho is rejected and Ha accepted, so it can be concluded that the partial variables Role of the Performance of the Teller has a significant influence on the variable Customer Satisfaction. Keywords : Customer Service, Tellers, Customer Satisfaction